A brewing public health crisis: antibiotic resistance - Adhikari, N. (Journal of Institute of Medicine Nepal, 2010)
Not Available; Editorial DOI: 10.3126/joim.v31i3.2971 Journal of Institute of Medicine Vol. 31, Issue 3, 2009, December Page: 1-2